Effect of frozen storage on the characteristics of a developed and commercial fish sausages - Al-Bulushi, I.; Kasapis, S.; Dykes, Gary; Al-Waili, H.; Guizani, N.; Al-Oufi, H. (2013)
The effect of frozen storage on the physiochemical, chemical and microbial characteristics of two types of fish sausages was studied. Fish sausages developed (DFS) with a spice-sugar formulation and commercial fish sausages (CFS) were stored at −20 °C for 3 months. Fresh DFS contained 12.22% lipids and had a 3.53 cfu/g total bacteria count (TBC) whereas, CFS contained 5.5% lipids and had a 4.81 cfu/g TBC. During storage, TBC decreased significantly (p < 0.05) in DFS whereas it did not change (p > 0.05) in CFS. A peroxide value (PV) was not detectable until week four and eight of storage in CFS and DFS, respectively. The salt-soluble proteins (SSP) level was stable in DFS but in CFS it declined significantly (p < 0.05). Colour values did not change significantly (p > 0.05) in both sausage types. This study showed that the effect of storage at −20 °C on fish sausages characteristics varied between formulations and depended on the ingredients of fish sausages.